Investigations on spatial distribution of low temperature plasma parameters using NiCr wire probe diagnostic - Naz, M.Y. (Elsevier B.V., 2016)
This study investigated the workability of a NiCr wire probe diagnostic under low temperature plasma operating conditions. The aim of the work was to design and fabricate a triple Langmuir probe with NiCr alloy for measurements in low temperature rf plasmas. The spatial distribution of electron temperature and number density were evaluated at different filling pressures in the range of 0.2-0.4 mbar and rf powers in the range of 200-400 W. The probe data revealed a linear increase in temperature and electron number density with rf power along the chamber centerline, whereas an inverse relationship was found between the given plasma parameters and filling gas pressure. The spatial distribution measurements showed a decreasing trend in plasma parameters at positions away from the chamber centerline. The probe I-V characteristics curve revealed a change in polarity of probe potential with an increase in current supply from the plasma discharge to the probe. Initially, the potential difference raised from highly negative values to zero volt, thereafter started increasing positively. It is found that the response of NiCr alloy as probe material was appreciably good under the proposed operating conditions. Â© 2016 Elsevier Ltd. All rights reserved.